La música como constructora de imaginarios comunicacionales: la generación de los poetas decapitados y el pasillo ecuatoriano del siglo xx - Guananga Pancho, Carla María (2014)
Ecuador is a country with a unique identity resulting from its diverse culture. This thesis, starting with an analysis of different communication theories that state the importance communication processes as transmitters and creators of culture, will focus on analyzing two essential elements of this process, music and literature. This process will be shown through a summary of the history of music in Ecuador; starting with the first aboriginal cultures, continuing with their adaptation to a new reality resulting from the Spanish conquest and concluding with the formation of the Republic and the appearance of new musical genres, such as, Pasillo. By studying the ¨beheaded generation¨ one will examine how literature mirrored the contemporary reality and how it influenced music. Finally, examining Jorge Araujo´s pasillo ¨Sendas Distintas¨, one will analyze music´s capacity to adapt to different contexts and fulfill its role as a creator of identity through communicational imaginaries.